Insights on the symbiotic associations of the tea shot hole borer (Coleoptera: Curculionidae) - Cruz, Luisa F.; Menocal, Octavio; Dunlap, Christopher; Cooperband, Miriam F.; Cloonan, Kevin R.; Tabanca, Nurhayat; Carrillo, Daniel (Frontiers in Microbiology, 2025)
IntroductionThe tea shot hole borer (TSHB), Euwallacea perbrevis (Schedl 1951) (Coleoptera: Curculionidae) is an invasive ambrosia beetle that carries multiple symbiotic fungi and vectors Fusarium spp. to avocado (Persea americana Mill.). This study investigated the role of six fungal species (Fusarium sp. FL-1, Fusarium sp. AF-8, Fusarium sp. AF-6, Graphium sp., Acremonium sp., and Acremonium murorum) as nutritional symbionts of TSHB, and the role of Fusarium species in plant pathogenicity.MethodsFour experimental approaches were used: (1) testing each of the six symbionts as a food source for TSHB larvae, (2) examining the stability of symbiotic associations by rearing TSHB on substrates previously colonized by individual fungi, (3) establishing TSHB colonies with single Fusarium symbionts (Mono-Fusarium Lines, MFL), (4) testing disease development in avocado trees infested with MFL.ResultsFusarium sp. FL-1 and Fusarium sp. AF-8 supported the highest percentage of larval development among the tested fungi. These two fungi persisted in the mycangia of beetles reared on a substrate pre-inoculated with other symbionts. In addition, both fungal species caused the largest lesions in avocado branches. TSHB feeding on the other tested symbionts (Fusarium sp. AF-6, Graphium sp., Acremonium sp. or Acremonium murorum) resulted in poor larval development and/or overall reduced reproduction compared to feeding upon Fusarium sp. FL-1 and AF-8 and the symbiont blend (control).DiscussionThese findings demonstrate the dual role of Fusarium sp. FL-1 and AF-8 as nutritional symbionts of TSHB and as key drivers of pathogenicity in avocado.